The Masar Project: Design and Development - Koo, Voon Chet; Chan, Yee Kit; Vetharatnam, Gobi; Lim, Tien Sze; Chung, Boon Kuan; Chuah, Hean Teik (PIER, 2005)
In 2002, the MASAR (Malaysian Airborne Synthetic Aperture Radar) project was initiated at Multimedia University (MMU), in collaboration with the Malaysian Centre for Remote Sensing (MACRES). The main objective of this project is to construct an instrument for earth resource monitoring in Malaysia. The proposed SAR system is a C-band, single polarization, linear FM radar. This paper outlines the major design issues and considerations for MASAR. In particular, the design and construction of the microwave system, microstrip antenna, and a high-speed data recording system are described. The SAR processing algorithm which incorporates motion compensation capability for high resolution image generation is also outlined.